OS5.5 Characteristics of high-grade gliomas with H3 G34 mutation in adults. (6th September 2019) - Picart, T; Barritault, M; Tabouret, E; Idbaih, A; Izquierdo Gracia, C; Poncet, D; Honnorat, J; Meyronet, D; Guyotat, J; Ducray, F
Abstract: BACKGROUND: H3 G34-mutant high-grade gliomas occur primarily in children but can also be encountered in adults. The aim of the present study was to describe the characteristics of H3 G34-mutant high-grade gliomas in adults. MATERIAL AND METHODS: We analysed the characteristics of 17 adult H3 G34-mutant high-grade gliomas and compared them with those of adult grade IV gliomas with H3 K27M mutation (n=21), IDH mutation (n=42) and TERT promoter (pTERT) mutation (n=88). RESULTS: Median age at diagnosis in H3 G34-mutant gliomas was 25 years (range: 19–33 y). All tumors had a hemispheric location. The radiological presentation was suggestive of a high-grade glioma in 6 patients but in 10 patients it initially suggested another diagnosis due to absent or faint contrast enhancement (n=9) or the presence of an initial intratumoral haemorrhage (n=1). In non- or faint contrast-enhancing cases, diffusion-weighted imaging (DWI) was more helpful to suspect an aggressive tumor than MR spectroscopy and perfusion MRI. All H3 G34-mutant gliomas were classified as IDH wildtype glioblastomas. PNET-like foci were observed in 8 cases and most cases were immunonegative for ATRX (92%) and Olig2 (81%) and demonstrated MGMT promoter methylation (82%). The clinical, radiological and histological presentation of H3 G34-mutant gliomas was different from that of midline H3 K27M-mutant diffuse gliomas and from that of IDH-mutant and IDH-wildtype pTERT-mutant glioblastomas. Median overall survival of G34-mutant gliomas was 23.9 months compared to 19.6 months (p=0.16), 13.7 months (p=0.45) and 58 months (p=2.3x10 -10 ) in H3 K27M-mutant diffuse gliomas, IDHwt pTERT-mutant and IDH-mutant glioblastomas, respectively. CONCLUSION: Adults H3 G34-mutant high-grade gliomas are associated with distinct characteristics and a poor prognosis. DWI seems helpful to identify cases that present as non-contrast enhancing lesions and can wrongly suggest another diagnosis in these young patients.